VARIASI LEKSIKAL DAN INOVASI FONOLOGIS DIASPORA INDIA - Siti Ulfa Rukmana; Subiyantoro Subiyantoro (PRASASTI: Journal of Linguistics, 2022)
The combination of native speakers and non-native speakers can make a distinctive language variety. The use of this variety is also found in Indian Diaspora in Medan. From this phenomenon, this study aims to investigate the language variations from a social point of view, in the form of age in Punjabi and Tamil ethnic in Medan. The data analysis used in this research is descriptive qualitative. The results of data analysis in this study are presented using lexical examples and how to pronounce them. The results show that there are distinctive variation of phonology and lexical at Punjabi and Tamil ethnic in Medan. In addition, the spoken variety of Medan city is more often used by the Indian diaspora aged 14-35 years and the use of standard Indonesian is more often used by aged less than14 years.